Bone Marrow Lesions in Athletic Stress Injuries: An Overview - Navas, Ana; Kassarjian, Ara (Seminars in Musculoskeletal Radiology, 2023)
This article discusses the presumed pathophysiology of osseous sport-related stress changes, the optimal imaging strategy for detecting the lesions, and the progression of the lesions as seen on magnetic resonance imaging. It also describes some of the most common stress-related injuries in athletes by anatomical location and introduces some new concepts in the field.
Keywords: bone; stress; sports; magnetic resonance imaging; fracture